Macrobenthic community of an anthropogenically influenced mangrove associated estuary on the East coast of India: An approach for ecological assessment - Nayak, Aswini; Equbal, Jawed; Rout, Sonali Sanghamitra; Dash, Bhagyashree; Thiruchitrambalam, Ganesh; Bhadury, Punyasloke; Satyanarayana, Behara; Raut, Dipti (Frontiers in Marine Science, 2022)
The Mahanadi Estuarine System (MES), with a complex network of freshwater channels, rivers, and mangroves, is a leading seaport in State Odisha on the east coast of India, but subjected to intense human activity in recent years. Such anthropic impingements are known to impact sediment-dwelling biota adversely. However, information on the macrobenthic community of the MES is not well documented yet. Therefore, the primary objectives of this study (February 2013-March 2017) were to address knowledge gaps on the macrobenthic community structure vis-à-vis local environmental conditions and to evaluate the extent of anthropogenic disturbances on macrobenthos. The results from 264 benthic grab samples (van Veen, 0.04 m2; 2 replicates × 12 GPS fixed locations × 3 seasons) revealed 73 taxa representing 64 genera and 48 families of macrobenthic fauna. The polychaetes (81.41%) and crustaceans (15.42%) were significant faunal groups that contributed mainly to the benthic population and diversity. Multivariate approaches using benthic community attributes and biotic indices (AMBI and M-AMBI) as proxy measures of environmental disturbances proved effective for appraisal. The correlations between the environmental parameters (temperature, pH, salinity) and community estimates were statistically significant. Hierarchical clustering analysis disclosed three major groups (Global R 0.70; p < 0.002) influenced by tolerant/opportunist species. The lower abundance, richness, diversity, and dominance of opportunistic species mark the signs of environmental stress. The community health status remained unbalanced, as indicated by AMBI scoring. M-AMBI analysis contributed best in differentiating areas exposed to diverse impacts and indicated polluted community health status with moderate ecological quality. Our results reiterate the effective use of macrobenthos as bioindicators for ecological status and monitoring. The findings could be utilized for future monitoring assessments, translated into valuable information, and designed into well-defined sustainable management strategies for the MES.